Development of an omentum-cultured oesophageal scaffold reinforced by a 3D-printed ring: feasibility of an in vivo bioreactor. (31st October 2018) - Chung, Eun-Jae; Ju, Hyung Woo; Yeon, Yeung Kyu; Lee, Ji Seung; Lee, Young Jin; Seo, Ye Been; Chan Hum, Park
Abstract: Current treatments of oesophageal diseases, such as carcinoma, congenital abnormality or trauma, require surgical intervention and oesophageal reconstruction with the stomach, jejunum or colon. However, serious side effects are possible with each treatment option. Despite tissue engineering promising to be an effective regenerative strategy, no functional solution currently exists for oesophageal reconstruction. Here, we developed an omentum-cultured oesophageal scaffold reinforced by a 3D-printed ring. The nano-structured scaffolds were wrapped into the omentum of rats and orthotopically transplanted for the repair of circumferential oesophageal defects two weeks later. The artificial oesophagus exhibited complete healing of the surgically created circumferential defects by the second week. The integration of the omentum-cultured oesophageal scaffold and the regenerative tissue remained intact. Macroscopically, there was no evidence of a fistula, perforation, abscess formation or surrounding soft-tissue necrosis. The omentum-cultured nano-structure scaffold reinforced by a 3D-printed ring is a more practical model with better vascularization for artificial neo-oesophagus reconstruction in a rat model.